The effect of building density on housing prices and the supply of housing in Stellenbosch: the application of a Hedonic Price Model. - Makhubu, Samkeliso Siphephelo (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2018.